Fundamentals of financial management - Brigham, Eugene (Canada : Thompson South-Western, 2004)
Fundamentals of Financial Management focuses on keeping readers abreast of these changes and acquainting them with the theoretical concepts and analytical tools in the field of financial management.
Part 1. Introduction to financial management -- Part 2. Fundamental concept in financial management -- Part 3. Financial Assets -- Part 4. Investing in long-term assets: capital budgeting -- Part 5. Capital structure and capital dividend policy -- Part 6. Working capital management -- Part 7. Special topics in financial management .
Includes index.
Keywords: CORPORATION